Formation of the spinel structure (AIAI₂О₄) phase on sapphire surface - Sidelnikova, N.S.; Rom, M.A.; Dan‘ko, A.Ya.; Nizhankovsky, S.V.; Sirik, U.V.; Krivonogov, S.I. (Functional Materials, 2004)
A phenomenon of transformation of sapphire surface layer with the formation of a new cubic phase of spinel (AIAI₂О₄) structure as a result of high temperature reducing annealing has been revealed. The result of microscopic investigations and X-ray diffraction analysis of the new phase layer on sapphire surface for two crystallographic planes (0001) and (1012 ) are presented. Обнаружено явление трансформации поверхностного слоя сапфира с образованием новой фазы с кубической структурой шпинели (AIAI₂О₄) в результате высокотемпературного восстановительного отжига. Приведены результаты микроскопических исследований и рентгеновского фазового анализа слоя новой фазы на поверхности сапфира для двух кристаллографических плоскостей (0001) и (1012). Виявлено явище трансформації поверхневого шару caпфipy з утворенням нової фази з ку6ічною структурою шпінєлі (AIAI₂О₄) у результаті високотемпературного відбудовного відпалу. Приведено результати мікроскопічних досліджень і рентгенівського фазового аналізу шару нової фази на поверхні сапфіру для двох кристалографічних площин (0001) i (1012).